2018
DOI: 10.1002/jbmr.3462
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Competing Risk of Mortality on Association of Cognitive Impairment With Risk of Hip Fracture in Older Women

Abstract: Previous studies examining the association of cognitive impairment and dementia with fracture outcomes in older adults have usually used standard approaches that did not take into account the competing risk of mortality. However, ignoring mortality may not provide accurate estimates of risk of fracture because dementia in older adults strongly predicts death, making mortality a competing risk. A total of 1491 women (mean age 87.6 years) participating in the prospective Study of Osteoporotic Fractures (SOF) Yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Osteoporotic fractures may cause morbidity and even mortality in the elderly [ 148 , 149 , 150 , 151 , 152 ]. Among osteoporotic fracture, hip fracture usually leads to hospitalization, disability, and even death [ 153 , 154 , 155 , 156 ]. Though there are considerable advances in the fracture risk assessment and the improvement of medication to decrease the risk of fragility fracture, many people with high fracture risk do not receive adequate investigation and treatment.…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…Osteoporotic fractures may cause morbidity and even mortality in the elderly [ 148 , 149 , 150 , 151 , 152 ]. Among osteoporotic fracture, hip fracture usually leads to hospitalization, disability, and even death [ 153 , 154 , 155 , 156 ]. Though there are considerable advances in the fracture risk assessment and the improvement of medication to decrease the risk of fragility fracture, many people with high fracture risk do not receive adequate investigation and treatment.…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…Another 10‐year follow‐up prospective cohort study ( 47 ) demonstrated that for women aged 75 years or older poor cognitive status (MMSE ≤ 23) was significantly associated with fractures (relative ratio [RR] 1.80, 95% CI 1.30–2.40), while for women aged 65 to 74 years this was not significant (RR 0.90, 95% CI 0.70–1.20). Most prospective studies ( 48–51 ) evaluating the association between cognition and fracture risk did not include rigorous evaluation of cognitive status ( 10 ) or used different tools when evaluating cognition, making it difficult to compare with our findings. Further, participants in the CLSA tended to be socially advantaged and healthier because those with low levels of literacy in English or French (including recent immigrants), or with hearing or memory problems were less likely to participate or score well on cognitive measures.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, given that all other cognitive measures evaluated in the current study were not associated with fractures, these results should be interpreted carefully and additional research is need to determine the association between cognition and fracture. The Study of Osteoporotic Fractures (SOF) Research Group ( 10 ) reported that women with mild cognitive impairment measured from comprehensive neuropsychological tests including Mini‐Mental State Examination (MMSE) had a 1.48‐fold higher risk of hip fracture (adjusted HR 1.48, 95% CI 0.98–2.28) but this was not statistically significant. Another 10‐year follow‐up prospective cohort study ( 47 ) demonstrated that for women aged 75 years or older poor cognitive status (MMSE ≤ 23) was significantly associated with fractures (relative ratio [RR] 1.80, 95% CI 1.30–2.40), while for women aged 65 to 74 years this was not significant (RR 0.90, 95% CI 0.70–1.20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings underscore a significant association between cognitive function and fracture risk, highlighting disparities across the axial and appendicular skeleton. This disparity points toward a multifaceted relationship between cognitive function, biomechanics, and bone quality [ 17 ]. Specifically, the axial skeleton, comprising regions such as the hip and spine, appears to derive greater benefits from cognitive processes.…”
Section: Discussionmentioning
confidence: 99%